2001
DOI: 10.1590/s0101-20612001000100024
|View full text |Cite
|
Sign up to set email alerts
|

Determining aflatoxins B1, B2, G1 and G2 in maize using florisil clean up with thin layer chromatography and visual and densitometric quantification

Abstract: 1 Recebido para publicação em 25/01/00. Aceito para publicação em 07/05/01. 2 ministério da agricultura e do abastecimento -laboratório de controle de qualidade e segurança alimentar/LAV/MG. Av. Raja Gabaglia, 245, BH, MG, Brasil, CEP 30380-090. email:gena@cdlnet.com.br; * A quem a correspondência deve ser enviada. SUMMARYA method for determining aflatoxins B 1 (AFB 1 ), B 2 (AFB 2 ),G 1 (AFG 1 ) andG 2 (AFG 2 ) in maize with florisil clean up was optimised aiming at one-dimensional thin layer chromatography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…Individual recovery values for densitometric analysis varied from 83.4 to 105.5% for all aflatoxins and from 67.5 to 101% for ochratoxin A. The recovery of aflatoxins from cereals achieved in the present study is similar with the results reported by Castro and Vargas (2001) and Kamimura et al. (1985).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Individual recovery values for densitometric analysis varied from 83.4 to 105.5% for all aflatoxins and from 67.5 to 101% for ochratoxin A. The recovery of aflatoxins from cereals achieved in the present study is similar with the results reported by Castro and Vargas (2001) and Kamimura et al. (1985).…”
Section: Resultssupporting
confidence: 90%
“…According to the European Commission 's Regulation, No 472/2002, amending (EC) Regulation No 466/2001, the maximum level accepted (MLA) for total aflatoxins is 4 mg/kg (for aflatoxin B 1 is 2 mg/kg) and for ochratoxin A is 3-5 mg/kg. Different screening methods and advanced techniques for detection and quantification of mycotoxins were reported in the last 20 years (Bauer and Gareis 1987;Richard et al 1993;Aziz et al 1998;Castro and Vargas 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…De Castro et al 149 set up a method for determining AFs in maize: AFs were extracted with chloroform:water (30/1, v/v) and purified with fluorisil cleanup for subsequent TLC analysis obtaining recoveries higher than 90%. AFB1 was similarly detected in maize using chloroform:water (250:25, v/v) as extraction solvent, followed by fluorisil cleanup and LC-FLD detection with 90% recoveries as well.…”
Section: Cerealsmentioning
confidence: 99%